High resolution data-independent acquisition with electron transfer dissociation mass spectrometry: Multiplexed analysis of post-translationally modified proteins - Sweredoski, Michael J.; Pekar Second, Tonya; Bröker-Lai, Jenny; Moradian, Annie; Heß, Sonja (International journal of mass spectrometry, 2015)
Data-dependent acquisition (DDA) mode is the most commonly used method in bottom-up proteomics. Recently, data-independent acquisition (DIA) modes have become popular alternatives because of their unbiased analysis, leading in general to more comprehensive, global qualitative profiling of proteome systems and also higher quantitative reproducibility in such profiling. Most of the previously established DIA methods are based on collision-induced dissociation (CID). However, when it comes to the analysis of labile post-translational modifications (PTMs), electron capture/transfer dissociation (ECD/ETD) may be better suited. In addition to the bottom-up approach, the middle-down approach, which analyzes peptides in the range of 3,000-10,000Da has emerged as an attractive alternative, including the analysis of highly modified and highly variable protein variants that exist in key system functions, such as histone signaling cascades. Here, we establish that a data-independent (DIA) middle-down ETD approach is a superior strategy in the differential characterization of PTM changes in histone H2B. We suggest that this strategy can further be used for other approaches where dynamic PTM characterization or changes due to different conditions are fundamental to accurate understanding of biological systems and function.
Gesehen am 25.06.2020